Inclusion Properties for Classes of p-Valent Functions - B. M. Munasser; A. O. Mostafa; T. Sultan; Nasser A. EI-Sherbeny; S. M. Madian (Journal of Function Spaces)
Making use of a differential operator, which is defined here by means of the Hadamard product, we introduce classes of p-valent functions and investigate various important inclusion properties and characteristics for these classes. Also, a property preserving integrals is considered.